The Influence of Intrinsic and Extrinsic Motivation on Employee Performance - Diny Wulansari; Mundakir Mundakir (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Employee performance is a critical determinant of service quality and operational success in hospitals. High-performing employees contribute directly to patient satisfaction, service efficiency, and overall institutional reputation. This study investigates the influence of intrinsic and extrinsic motivation on the performance of employees at Petrokimia Gresik Hospital, aiming to provide empirical evidence to guide strategic human resource management in healthcare settings. A quantitative research design was employed, with data collected using structured questionnaires. The respondents consisted of 85 permanent employees selected through simple random sampling, ensuring that the sample fairly represented the hospital's workforce. The questionnaire was designed to measure aspects of both intrinsic motivation (such as self-fulfillment, recognition, and meaningful work) and extrinsic motivation (such as salary, benefits, and job security), along with indicators of employee performance. Data were analyzed using multiple linear regression analysis to examine the individual and joint effects of the motivational variables on performance. The results revealed that both intrinsic motivation (β = 0.532, p < 0.05) and extrinsic motivation (β = 0.487, p < 0.05) had a statistically significant and positive impact on employee performance. The model showed that the combination of these two factors accounted for 68.2% of the variation in employee performance (R² = 0.682), indicating a strong explanatory power. These findings underscore the importance of a balanced motivational strategy in hospital management. Relying solely on financial incentives is insufficient; efforts must also be made to cultivate a positive and fulfilling work environment. Therefore, hospital administrators are encouraged to design integrated motivation programs that address both intrinsic and extrinsic factors to enhance employee engagement, productivity, and ultimately, the quality of healthcare services provided.